Coal, its role in tomorrow's technology a sourcebook on global coal resources - Simeons, Charles (Pergamon Press, 1978)
Coal: Its Role in Tomorrow's Technology: A Sourcebook on Global Coal Resources focuses on the increasing consideration of coal as an alternative energy source, taking into consideration the mining, production, and research and development programs of various countries on this mineral. The book first offers information on energy demand, particularly noting the increasing consumption of energy around the world. The experience of the United States in meeting its energy demand through importation of oil and natural gas is discussed. The manuscript then examines the sources of coal and other resources, including types and properties of coal and disturbances in coal seams. The publication takes a look at the state of industries and coal production capabilities of various countries, such as the USSR, China, India, Poland, Australia, South Africa, and Canada. The text also considers the national research and development programs of the USSR, United States, China, India, Poland, France, and other countries on coal preparation, monitoring, and production. The manuscript discusses modern exploration programs on coal, mining plants and equipment, gasification of coal, and conversion of chemicals from coal. The text is a primary reference for readers interested in studying coal as an alternative energy source.--Provided by publisher.